2019
DOI: 10.1016/j.cell.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Microenvironment Shapes the Intratumoral Architecture of Pancreatic Cancer

Abstract: Highlights d Cancer-associated fibroblasts contribute to pancreatic cancer heterogeneity d Cancer cells can have a double-positive phenotype: proliferation and invasion d High CAF abundance linked with DP cells enriched for MAPK and STAT3 co-signaling d Intra-tumoral gland types provide tissue heterogeneity linked with clinical outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
336
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(364 citation statements)
references
References 45 publications
9
336
0
Order By: Relevance
“…Tumor grading did not reveal an association with animal survival (median survival 155 days versus 187 days, log-rank p = 0.09; Figure 1B). Importantly, diverse grading of KPC-derived tumors resembles PDAC heterogeneity as observed in patients [26,30]. Together, these results demonstrated no prognostic value of tumor grading based on overall survival in the KPC cohort.…”
Section: Association Of Tumor Grading and Survival Not Confirmedmentioning
confidence: 74%
See 1 more Smart Citation
“…Tumor grading did not reveal an association with animal survival (median survival 155 days versus 187 days, log-rank p = 0.09; Figure 1B). Importantly, diverse grading of KPC-derived tumors resembles PDAC heterogeneity as observed in patients [26,30]. Together, these results demonstrated no prognostic value of tumor grading based on overall survival in the KPC cohort.…”
Section: Association Of Tumor Grading and Survival Not Confirmedmentioning
confidence: 74%
“…PDAC heterogeneity does not only cover the mutational landscape of epithelial tumor cells, but also affects the tumor microenvironment and ECM composition [30]. Major ECM proteins of the PDAC microenvironment include collagen and HA.…”
Section: Quantity Of Collagen and Hyaluronic Acid Is Not Associated Wmentioning
confidence: 99%
“…The authors also reported that loss of ROBO2 with concomitant increased ROBO1 expression signalling was correlated with poor disease-free survival in patients with PDAC [119]. In addition, Ligorio and colleagues recently reported that mitogen-activated protein kinase (MAPK) and STAT3 signalling is upregulated in a subpopulation of highly proliferative and invasive PDAC cancer cells, and that this phenotype is due to CAF-derived paracrine TGFb signalling [121]. Collectively, these studies suggest that IL-1 and/or TGF-b could be targeted to reduce the proportion of the prometastatic CAF subpopulations in vivo, therefore impairing tumourigenesis ( Figure 5A).…”
Section: Targeting Interactions Between Cafs and Their Surrounding MImentioning
confidence: 95%
“…Increased tension between tumor cells resulted in elevated FAK1 signaling, increased phosphorylated-STAT3 and increased fibrosis, which were again reduced following FAK1 inhibition (Laklai et al, 2016). Further evidence reinforces the relationship between CAF, STAT3 signaling, and PDAC progression as a recent study elucidated that CAFs induce PDAC tumor cellintrinsic STAT3 signaling, resulting in a more invasive and proliferative phenotype (Ligorio et al, 2019). These studies reveal the tight association between stroma and tumor in promoting tumor progression and support the notion that a fibrotic stroma can contribute to exclusion of cytotoxic T cells.…”
Section: Recruitment Of Immunosuppressive Populationsmentioning
confidence: 54%